BeSiDe time to move behavior support in dentistry from an art to a science: A position paper from the BeSiDe (Behavior Support in Dentistry) Group. (29th July 2021) - Mac Giolla Phadraig, Caoimhin; Newton, Tim; Daly, Blánaid; Limeres Posse, Jacobo; Hosey, Marie Therese; Yarascavitch, Carilynne; MacAuley, Yvonne; Buchanan, Heather; Nunn, June; Freeman, Ruth; Stirling, Chris; Healy, Olive; et al.
Abstract: Aims: To share the need for agreement in terminology around how people are supported to receive dental care. Method: In this position paper, we make the case for a shift in behavior support in dentistry from an art to a science. Results: We outline why we need agreement on the definition of behavior support across dentistry, agreement on underlying theory, aims and values, and why we need agreement on terms for specific techniques. Conclusions: We share how patients and dental teams can benefit through better science, education and practice of dental behaviour support.